Dynamic Reliability Evaluation of Linear Consecutive k-out -of-n: F System With Multi-State Components - Gokdere, Gokhan; Gurcan, Mehmet (E D P Sciences, 2018)
In engineering applications, analyzing a technical system vary according to the operating principles of the system. In some situations, the status of the system is a function of stresses which act on the system and cause degradation. In order to efficiently analysis the reliability of a system which operates under stress, assigning the various states to the components depending on their operating performance is very important. In this paper, we have investigated the linear consecutive k-out-of-n: F system and assigned multiple states to its components. Due to the reason, the operating performance of the components can easily be controlled. Apart from that the reliability of the system depending on the states of its components can be calculated at any time interval. In the numerical example, the states of the components and the reliability calculation of the system at specific time intervals are shown clearly.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS